Artificial Synapses: Near‐Infrared‐Irradiation‐Mediated Synaptic Behavior from Tunable Charge‐Trapping Dynamics (Adv. Electron. Mater. 2/2020). (13th February 2020) - Wang, Yan; Yang, Jing; Ye, Wenbin; She, Donghong; Chen, Jinrui; Lv, Ziyu; Roy, Vellaisamy A. L.; Li, Huilin; Zhou, Kui; Yang, Qing; Zhou, Ye; Han, Su‐Ting
Abstract : In article number 1900765, Vellaisamy A. L. Roy, Ye Zhou, Su‐Ting Han, and co‐workers demonstrate a photonic synaptic transistor based on a tunable charge‐trapping medium. The device senses and responds to near‐infrared light signals, and can mimic memorization and dynamic forgetting processes, enabling device‐level synaptic evolution from short‐term to long‐term neuroplasticity.